Multilocus Sequence Typing and Antifungal Susceptibility of Vaginal and Non-vaginal Candida glabrata Isolates From China - Chen, Yisheng; Wu, Yongqin; Lulou, Kaiyi; Yao, Dongting; Ying, Chunmei (Frontiers in Microbiology, 2022)
Candida glabrata is a common cause of Candida infections. In our present study, we investigated the antifungal susceptibility and molecular epidemiology of vaginal and non-vaginal C. glabrata isolates. Seventy-six vaginal C. glabrata strains isolated from patients with vulvovaginal candidiasis (VVC) and 57 non-vaginal C. glabrata isolates were collected at two hospitals in Shanghai, China. Antifungal susceptibility was examined using a broth microdilution method. Multilocus sequence typing (MLST) was used for genotyping. Overall, 28 (21.1%), 28 (21.1%), and 29 (21.8%) C. glabrata isolates were resistant to fluconazole, itraconazole, and voriconazole, respectively. Briefly, 18 (23.7%), 18 (23.7%), and 19 (25%) vaginal strains were resistant to fluconazole, itraconazole, and voriconazole. While, resistance to these antifungals were all 17.5% (10/57) in non-vaginal strains. All isolates retained susceptibility to amphotericin B, and only four non-vaginal isolates were caspofungin resistant. Genotyping identified 17 ST patterns. In non-vaginal samples the same genotypes appear as in the vagina, except for one genotype, ST-182, while in vagina samples more genotypes appear, ST8, ST19, ST45, ST55, ST66, ST80, ST138, and ST172. The most common genotype was ST7 (81 strains), followed by ST10 (14 strains), and ST15 (11 strains). The majority of resistant phenotype strains (25/30, 83.3%) correlated to the predominant genotype (ST7), and the rest belonged to ST3 (2/30, 6.7%), ST10 (1/30, 3.3%), ST19 (1/30, 3.3%), and ST45 (1/30, 3.3%). Our survey revealed cross-resistance in vaginal and non-vaginal C. glabrata isolates. Moreover, there is no genotype associated with resistance phenotype. Keywords: Candida glabrata, multilocus sequence typing (MLST), vulvovaginal candidiasis, antifungal susceptibility, fluconazole, cross resistance, genotype diversity